A DECOLONIZED CURRICULUM FOR PRIMARY TEACHERS: REFRAMED UNITS OF CHANGE (EDUCATION IN THE 21ST CENTURY, 2022)
It is evidenced (Purri 2020) that the impact on the British psyche of having ruled so much of the world has neither faded nor has it been faced. British primary schools in the main tend not to teach imperial history, leaving British children lacking detailed historical knowledge of their country’s imperial past. Schools largely steer clear of the subject of the Empire, ‘perhaps because there is no consensus as to whether to present the facts in a positive or negative light, and because neutrality is a difficult stance to adopt, given the intense passions the subject evokes. In multicultural Britain, many families have direct family experiences of being at the receiving end of colonialism. Conversely, when Britons were polled by YouGov (2014) about whether they think of the British Empire as something to be proud of, 59% agreed that it was (Puri 2020, p.75-76).
Keywords: education; curriculum; primary school; pedagogical concept; teaching programme